Thermal Conductivity Of Lightweight Concrete Block With Various Cooling Agent - A. Majid, Masni; Roslan, Aina Syafawati; Abdul Hamid, Noor Azlina; Salleh, Norhafizah; Jamellodin, Zalipah (International Journal of Integrated Engineering, 2020)
Energy was the important sources to human life. Due to increases energy demand in daily life, the energy consumption was increase day by day because of the heat load from solar radiation and heat produced by people. Toward sustainable development, this research was carried out to develop a lightweight concrete (LWC) block with various cooling agent such as glycerine, propylene glycol, coconut shell and gypsum powder. Six lightweight concrete (LWC) block with the size 250mm (L) Ã— 250mm (W) Ã— 100mm (T) were tested for thermal conductivity value. From the experimental result, it shows that lightweight concrete (LCW) block with various cooling agent obtained thermal conductivity value of 0.17W/mK - 0.36W/mK lower than thermal conductivity value for normal lightweight concrete (0.8W/mK) depending on concrete density. The lightweight concrete (LCW) block with cooling agent having low thermal conductivity value will reduce energy consumption in building.